Effects of pre-slaughter fasting on broiler welfare, meat quality, and intestinal integrity - Pereira, R. E P [UNESP] (2013)
The Brazilian Ministry of Agriculture (MAPA) regulations establish 12 hours as the maximum pre-slaughter fasting period for broilers; however, many processing plants have considered this time is not sufficient, and consequently return the birds to the farms, with consequent economic losses and welfare problems. Therefore, it is necessary to investigate the possible effects of longer pre-slaughter fasting times. The objective of the present study was to evaluate the effect of pre-slaughter fasting times longer than those established by MAPA on broiler welfare, breast meat quality, and intestinal integrity. Forty 42-d-old broilers were submitted to different pre-slaughter fasting times: group I: 6 hours, group II 9h, group III 12h, and group IV 15h. Bird welfare was assessed before slaughter. After sacrifice, intestinal samples were collected to assess their morphology and morphometrics, and the Pectoralis major muscle was analyzed for pH and color. There was no influence (p>0.05) of treatments on breast muscle pH or color.There were no significant changes in intestinal morphometrics (p<0.05). Bird behavior was affected (p<0.05), suggesting that welfare was impaired as fasting time increased, but no differences in the analyzed parameters were detected between broilers fasted for 12 or 15 hours. It was concluded that the behavioral differences between birds fasted for 12 and 15 hours are not sufficient to assert that those fasted for 15 hours were in worse welfare conditions.